1989
DOI: 10.1093/nar/17.6.2261
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of 2-pyrimidinone nucleosides and their incorporation into oligodeoxynucleotides

Abstract: The synthesis of 1-(beta-D-2'-deoxyribosyl)-2-pyrimidinone (dK) and its 5-methyl derivative (d5) from 2'-deoxycytidine or 2'-deoxythymidine, respectively, via silver oxide oxidation of 4-hydrazinopyrimidines is described. The necessary hydrazine substituted pyrimidine nucleosides have been prepared by transamination of a protected cytidine derivative or by addition/elimination reactions to an O4-sulfonated thymidine derivative. Oxidation of the 4-hydrazino pyrimidines was complicated by a competing hydrolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
4
55
1
Order By: Relevance
“…By modulating the DNA duplex stability through 'anomalous' base pairs and measuring their effect on the free energy of binding, we were able to correlate the stability of the duplex with the stability of the protein-DNA complex. Previously published reports showed that the DNA duplex stability can be altered by replacing the C paired with 2AP by the T base, resulting in a higher melting temperature for the DNA (31)(32)(33)38). The reason for the increased DNA stability is apparent from NMR studies which showed that the 2AP-C forms a partially charged species to accommodate the pairing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By modulating the DNA duplex stability through 'anomalous' base pairs and measuring their effect on the free energy of binding, we were able to correlate the stability of the duplex with the stability of the protein-DNA complex. Previously published reports showed that the DNA duplex stability can be altered by replacing the C paired with 2AP by the T base, resulting in a higher melting temperature for the DNA (31)(32)(33)38). The reason for the increased DNA stability is apparent from NMR studies which showed that the 2AP-C forms a partially charged species to accommodate the pairing.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were at positions 9 and 11 on To further assess the role of duplex stability on the bimolecular process, we measured the affinity of the repressor protein for operator when the lac operator was substituted with 2-aminopurine-uracil base pairs (2AP.U) instead of the 2-aminopurine.cytosine. Thermal denaturation experiments have shown that duplexes containing 2AP paired with thymine are more stable than duplexes containing 2-aminopurine paired with cytosine (31)(32)(33). The use of the uracil analogue was dictated by the need to mimic the structure of cytosine which does not contain a 5-methyl group in the major groove.…”
Section: Competition Equilibrium Dissociation Assaysmentioning
confidence: 99%
“…Recently it has been shown that 2'-deoxyzebularine triphosphate (dZTP) is incorporated by DNA polymerases opposite to guanine (G) and when Z is at the template it directs dGTP incorporation [5]. In spite of the absence of the amino group, 2'-deoxyzebularine behaved similar to 2'-deoxycytidine pairing with guanine [5][6][7]. In this report we describe the melting behaviour of DNA duplexes carrying the 1, 2-dihydropyrimidin-2-one (Z) residue opposite to all four natural bases.…”
Section: Synthesis and Hybridization Properties Of Modified Oligodeoxmentioning
confidence: 99%
“…Pyrimidine nucleoside analogues of 2'-deoxycytidine (98) and thymidine (100) each lacking the functional group para to the glycosidic linkage (99 and 101, respectively) [242] were synthesized in order to quantify the contribution of these functional groups to duplex stability. Additional modified pyrimidine nucleosides incorporated into oligonucleotides are 04-methyl-or 04-ethylthymidine (m4T or et4T, 102),[2431 2'-deoxyuridine (dU, 103),[2271 5-methylcytidine (m5dC, 104),1227, 2441 the pyridopyrimidine nucleoside mentioned already (10512311) and a similar compound which is able to pair with several nucleobases (106[2451), 5-putrescinylthymidine (107) as well as some other 5-substituted thymi dine^,^'^^] which occur in bacteriophages and inhibit nuclease digestion, and an oligonucleotide with 5-azacytidine (z5dC, 108) (or 5,6-dihydr0-5-azacytidine~'~~'); thus, the pyrimidine field, too, presents compounds modified in the aromatic nucleus of the nucleobases.…”
Section: Modified Oligonucleotides As Substrates For Nucleases and Pomentioning
confidence: 99%